Maternal Risk Factors Associated with Low Birth Weight: A Case Control Study in Deli Tua District - Nur Mala Sari; Peny Ariani; Putri Ayu Yessy Ariescha (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Low birth weight (LBW) remains a significant public health concern in Indonesia, contributing to neonatal morbidity, mortality, and long-term developmental challenges. Although numerous studies have explored LBW, evidence on maternal risk factors in low-resource settings particularly within independent midwife practices remains scarce. This study examined the associations between maternal age, parity, antenatal care (ANC) visits, history of anemia, and gestational weight gain with LBW incidence in Deli Tua Sub-District, Deli Serdang Regency. A case-control design was employed from December 2024 to March 2025, involving 95 postpartum mothers (35 cases, 60 controls) selected through purposive sampling. Data were collected using validated questionnaires (Content Validity Index = 0.82; Cronbach's α = 0.85) and maternal health records, and analyzed using Chi-square tests and multivariate logistic regression (SPSS version 22). Multivariate analysis identified maternal age at risk (<25 or >35 years) as the sole significant predictor of LBW (OR = 6.69; 95% CI = 3.21-25.22; p = 0.006). Parity (OR = 2.76; p = 0.077), ANC visits (OR = 1.22; p = 0.797), history of anemia (OR = 0.57; p = 0.421), and gestational weight gain (OR = 1.20; p = 0.773) were not significantly associated with LBW. The model demonstrated acceptable fit (Hosmer Lemeshow p = 0.49; Nagelkerke R² = 0.29). Maternal age emerged as the most influential determinant of LBW in this population. These findings underscore the importance of targeted surveillance for high-risk age groups and the enhancement of promotive and preventive strategies including improved ANC service quality, nutritional counseling, and family engagement in maternal care to reduce LBW incidence in resource-limited settings. Keywords: Anemia, Antenatal Care, Gestational Weight Gain, Low Birth Weight, Maternal Age, Parity